THU0593 Frequency and Impact of Disease Symptoms Experienced by Patients with Systemic Sclerosis: A Comparison among Five European Countries. (23rd January 2014) - Willems, L. M.; Kwakkenbos, L.; Leite, C.; Thombs, B. D.; van den Hoogen, F. H.; Maia, A.; van den Ende, C. H.
Abstract : Background: Systemic sclerosis (SSc) is a complex autoimmune disease with heterogeneous manifestations. The symptoms experienced by patients with SSc are important targets for health professionals like physiotherapists and occupational therapists. Objectives: 1) To compare the prevalence in symptoms and their impact on daily functioning; and 2) to compare the use of physiotherapy and/or occupational therapy reported by patients with SSc across five European countries. Methods: Patients with SSc across Europe were invited to complete an online survey through announcements by European patient associations. The survey was based on a Canadian questionnaire [1 ] consisting of questionnaires on sociodemographics, disease characteristics, quality of life, the prevalence and impact of 40 symptoms, and the use of physiotherapy and occupational therapy. Differences in frequency and impact of SSc symptoms among countries were examined by determining 95% confidence intervals (CIs) using the method recommended by Agresti and Coull [2 ]. Countries with more than 50 responding participants were included in the analyses. Results: In total, 569 patients were included in the analyses, living in the Netherlands (N= 240), France (N= 123), the United Kingdom (N= 92), Spain (N= 61), and Switzerland (N= 53). The five most frequently reported symptoms (% (range among countries)) were fatigue (76%–96%), Raynaud's phenomenon (83%–98%), joint pain (80%–92%), muscle pain (70%–86%), and shortness of breath (65%–86%). French and Dutch participants more often reported fatigue than Spanish patients (96%, 95% and 76%, respectively), whereas Spanish participants more often reported shortness of breath than Dutch patients (86% and 65%, respectively). Furthermore, if present, difficulty walking, swollen joints, and joint pain affected most frequently daily functioning. Use of physiotherapy and/or occupational therapy ranged from 48% (the Netherlands) to 21% (Switzerland). In the Netherlands and in France use of physiotherapy and/or occupational therapy was associated with the number of symptoms (r = 0.17, P = 0.01 and r = 0.25, P = 0.01, respectively). Conclusions: European patients with SSc experience a broad range of symptoms with impact on daily functioning. There is a substantial variation in the use of physiotherapy and occupational therapy across the European countries. The results suggest that the provided care delivered by a physiotherapist or an occupational therapist is not yet optimally tuned to the needs of the patient in all countries. References: Bassel M, Hudson M, Taillefer SS, Schieir O, Baron M, Thombs BD. Frequency and impact of symptoms experienced by patients with systemic sclerosis: results from a Canadian National Survey. Rheumatology 2011; 50: 762-7. Agresti A, Coull BA. Approximate is better than "exact" for interval estimation of binomial proportions. Am Stat. 1998; 52: 119-26. Disclosure of Interest: None Declared